Quantifying Stimulus-Affected Cinematic Spaces Using Psychophysiological Assessments to Indicate Enhanced Cognition and Sustainable Design Criteria - Sakhaei, Hamidreza; Yeganeh, Mansour; Afhami, Reza (Frontiers in Environmental Science, 2022)
Objectives Converging architecture with media and cognition has proved to be a practical approach to scrutinizing architectural elements’ significant contribution to engineering science. In this research, a behavioral analysis has been conducted to examine if disruptive events in cinematic spaces can lead to an insightful perception of architectural qualities and enhanced interplay with observed space to highlight sustainable design characteristics. Methods Qualitative and quantitative assessments such as personality traits, positive and negative affect, feeling chills, pleasure, arousal, dominance, physiological responses alongside space quality measurements were integrated for participants (N=90) while watching three films spaces with respective increasing stimuli to facilitate space configuration analysis. Results Analyses shows that the space with intensive disruption of architectural elements successfully indicated improved cognitive perception of spatial qualities, more interaction, and signified sustainable design criteria. Conclusion It has been concluded that evoking events significantly disrupted the banalization of cinematic spaces, illustrating that the designed model can indicate a more homogenous evaluation of sustainable environment criteria.